1997
DOI: 10.1002/(sici)1097-0185(199710)249:2<206::aid-ar7>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of air pollution in the pulmonary surfactant system of the pigeon (Columba livia)

Abstract: Background: The integrity of both pulmonary surfactant and surfactant producing cells, type II pneumocytes, is essential for normal pulmonary function. Almost all studies about air pollution effects on the pulmonary surfactant system have been performed by biochemical techniques, using atmospheric pollutants in a much higher concentration than that found in polluted city air. A comparative study of the number of lamellar bodies (LB) (pulmonary surfactant precursors) from type II pneumocytes of pigeon lungs bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In this respect, the observed increase in size of parabronchial epithelium and the vacuolized aspect of the cytoplasm may be a consequence of the uptake of surfactant by pneumocytes during the early defence against bacterial infection and the preparation for reactive changes in the lung. It is noteworthy that the avian type-II pneumocyte is present in the parabronchial epithelium, which lines the central lumen (Lorz and Lopez, 1997). However, it must be kept in mind that concerning the origin, the composition and structure and the metabolism major differences exist between mammalian and avian lung surfactants (Scheuermann et al, 1997) and surfactant proteins (Bernhard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the observed increase in size of parabronchial epithelium and the vacuolized aspect of the cytoplasm may be a consequence of the uptake of surfactant by pneumocytes during the early defence against bacterial infection and the preparation for reactive changes in the lung. It is noteworthy that the avian type-II pneumocyte is present in the parabronchial epithelium, which lines the central lumen (Lorz and Lopez, 1997). However, it must be kept in mind that concerning the origin, the composition and structure and the metabolism major differences exist between mammalian and avian lung surfactants (Scheuermann et al, 1997) and surfactant proteins (Bernhard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This induction of oxidative stress puts great emphasis on the use of antioxidants for PQ resistance (Suntres 2002) and makes it suitable for testing the efficiency of carotenoids in this respect. Furthermore, irrespective of intake route, PQ accumulates in the internal organs (Autor 1977) and creates respiratory oxidative stress as inhaled air pollution (Lorz & Lopez 1997;Dales et al 2006;de Kok et al 2006), which makes the experiment a direct test of the role of pollutioninduced oxidative stress for our previously documented variation in plumage colour between urban and rural birds (Isaksson et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…From these studies it was estimated that alveolar macrophages in mice or rats were 20 times more frequent compared to FARM in the lung of the much larger chicken [46,79]. Some earlier studies even reported on a complete failure to obtain free avian respiratory macrophages through lung lavage [37,39,65]. In this context it should be noted that FARM obtained through lung lavage are not only derived from the surface 318 S. Reese et al…”
Section: The Phagocyte System Of the Avian Lung And Air Sacsmentioning
confidence: 99%
“…From this work the picture emerges that the epithelium and the interstitial macrophages of the atrial and infundibular area play an important role in the removal of particles from the air on their way to the thin, extensive and highly vulnerable tissue of the gas exchange area [55]. With surface phagocytic cells at the atrial and infundibular levels [42,46], subepithelial phagocytic cells and interstitial macrophages [32,39,72] and resident pulmonary intravascular macrophages [46], birds appear to possess a highly diversified pulmonary defence armoury [42]. Unfortunately, the pathway of antigen uptake and processing in the chicken lung has not been studied to date.…”
Section: Particle Uptake In the Avian Lung And Air Sacsmentioning
confidence: 99%